PENINGKATAN KREATIVITAS SISWA PAUD KUTILANG BANTEN MELALUI FASILITAS SUDUT KREATIF - Adisti Ananda Yusuff; Indra Gunara Rochyat; Erina Wiyono; Harlinda Syofyan (Institut Seni Indonesia Surakarta, 2024)
PAUD Kutilang is one of the kindergartens (PAUD) located in Petir Village, Kadugenep, Banten Regency, which currently has 40 students divided into 3 groups: Play Group, Group A, and Group B. The pre-existing conditions after the PKM (Community Service) Team conducts a situation analysis and approaches to needs and problems, the team found several problems: 1) the school does not have a work storage facility, 2) the lack of book storage facilities, and 3) educational toy storage. Therefore, the steps taken focus on adding facilities and educating students about position placement using ergonomic and anthropometric standardization appropriate for PAUD students. The purpose of this PKM activity is to help create comfort in classroom activities through the addition and improvement of supporting facilities for teaching and learning activities to improve thinking, reading skills, and learning enthusiasm for the students of PAUD Kutilang, Banten with the expertise of each member involved in this PKM activity. This PKM activity resulted in the addition of a facility that is used to increase the creativity of Kutilang PAUD students in carrying out teaching and learning activities in the classroom, not forgetting that the PKM Team also provides a little knowledge about ergonomics for children to provide new insights for teachers in classroom activities. Hopefully, this PKM activity can increase new insights and experiences for students and teachers at PAUD Kutilang Banten